Wittgensteinian Facts as Ultimate Items of Tractarian Ontology?. Issue 3 (3rd July 2018) - Felappi, Giulia
ABSTRACT: According to Zalabardo, Wittgenstein in TLP solves the metaphysical problem of the unity of facts by holding that facts are the only ultimate items of Tractarian ontology. With his intriguing proposal, Zalabardo has both interpretative and theoretical aims and in my commentary I will similarly discuss both aspects of Zalabardo's Tractarian ontology.